2019
DOI: 10.1021/acsomega.9b02427
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Cutaneous Substitutes Based on Poly(l-co-d,l-lactic acid-co-trimethylene carbonate) with Schinus terebinthifolius Raddi Extract Designed for Skin Healing

Abstract: The search for new therapies and drugs that act as topical agents to relieve pain and control the inflammatory processes in burns always attracted interest in clinical trials. As an alternative to synthetic drugs, natural extracts are useful in the development of new strategies and formulations for improving the quality of life. The aim of this study was to develop a wound dressing using poly(l-co-d,l-lactic acid-co-trimethylene carbonate) (PLDLA-TMC) containing Schinus terebinthifolius Raddi (S.T.R.). S.T.R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…The osteoinductive properties is a characteristic that must be evoked in a material, and not only the biocompatibility itself such as adhesion and proliferation. Additionally, this new material (patent pending of our laboratory 21 ), can be processed in different forms to possess a variety of approaches (even for skin healing as recently published by Komatsu et al 7 In this work, the successful 3D printing process of PLDLA-TMC gives rise to assorted new designs of this material for bone formation, since one can modulate parameters of porosity and shape of the obtained device.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The osteoinductive properties is a characteristic that must be evoked in a material, and not only the biocompatibility itself such as adhesion and proliferation. Additionally, this new material (patent pending of our laboratory 21 ), can be processed in different forms to possess a variety of approaches (even for skin healing as recently published by Komatsu et al 7 In this work, the successful 3D printing process of PLDLA-TMC gives rise to assorted new designs of this material for bone formation, since one can modulate parameters of porosity and shape of the obtained device.…”
Section: Discussionmentioning
confidence: 92%
“…It was developed by our research group as a promising material, due capacity of PLDLA to its biological reabsorption abilities and biocompatibility. Previous studies in recent literature related to PLDLA-TMC based-materials in skin tissue regeneration 7,8 and tendon 9 demonstrated that the terpolymer is versatile in a wide range of medical applications, as well as presenting biocompatibility characteristics. Furthermore, the TMC shows flexibility and degradation rates consistent with the applications designed to bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In the results of immunohistochemistry with the specific molecular marker for the inflammatory response, CD68, capable of identifying macrophages, it was verified that in all treated groups (7 or 14 days) there was an expressive detection of positivity for macrophages (Table 5, p > .05 compared to control) corroborates the evolution in the tissue repair process, since the literature shows that poor macrophage response impairs healing and wound closure, as the potential participation of macrophages leads to fibrotic tissue and efficient tissue repair. [48][49][50] Unlike the results obtained by Komatsu et al 51 who demonstrated weak CD68 labeling in the dermal wound scab of treated rodents when treated with Schinus terebinthifolius Raddi extract.…”
Section: Immunohistochemical Analyzes Of Skinmentioning
confidence: 71%
“…All samples submitted to microscopy were cultured in Thermanox ® coverslips (Nunc Thermo Scientific, Rochester, NY, USA). Cell proliferation and viability were evaluated after 1 and 3 days, as described by Komatsu et al (2019) [20]. Cells were subjected to fluorescence live imaging (Live/Dead KIT) and analyzed by laser scanning confocal microscopy (LSCM) (model TCS SP8; Leica Microsystems GmbH, Heidelberg, Germany).…”
Section: Cell Survival and Morphologymentioning
confidence: 99%